2017
DOI: 10.1111/jocn.13996
|View full text |Cite
|
Sign up to set email alerts
|

Combining clinical practice and academic work in nursing: A qualitative study about perceived importance, facilitators and barriers regarding clinical academic careers for nurses in university hospitals

Abstract: A culture change would require a show of leadership that would promote and enable combined research, teaching and clinical practice and that would introduce clinical academic career pathways for nurses. Meanwhile, nurse academics should collaborate with established medical academics for whom combined roles are mainstream, and they should take advantage of their established infrastructure for success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(138 citation statements)
references
References 25 publications
4
133
0
1
Order By: Relevance
“…The RNs perceived that many nurse managers did not have knowledge of what competence they as RNs with a PhD had, and what they could contribute to in terms of improving nursing care. This is also described by nurse managers (van Oostveen et al, ). Rather, nurse leaders have been found to not value postgraduate degrees as contributing to improvements in nursing practice and clinical outcomes (van Oostveen et al, ; Wilkes & Mohan, ).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The RNs perceived that many nurse managers did not have knowledge of what competence they as RNs with a PhD had, and what they could contribute to in terms of improving nursing care. This is also described by nurse managers (van Oostveen et al, ). Rather, nurse leaders have been found to not value postgraduate degrees as contributing to improvements in nursing practice and clinical outcomes (van Oostveen et al, ; Wilkes & Mohan, ).…”
Section: Discussionmentioning
confidence: 72%
“…Rather, nurse leaders have been found to not value postgraduate degrees as contributing to improvements in nursing practice and clinical outcomes (van Oostveen et al, ; Wilkes & Mohan, ). Similar difficulties in terms of limited employment opportunities for RNs with a PhD to work in clinical practice have been reported (van Oostveen et al, ; Wilkes & Mohan, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, known challenges include limited awareness of how to progress as a researcher, lack of time, funding, support, research infrastructure, knowledge and skills (Van Oostveen et al, 2017;White et al, 2013).…”
Section: Creating a Personalised Tapestrymentioning
confidence: 99%
“…Publications on strategies to improve recruitment rates, 26,27 to retain participants in clinical research, [27][28][29] and to facilitate researcher-clinician collaboration 30,31 reported difficulties in combining clinical and research roles, where the main reasons were the lack of time, ethical concerns, 32 and absence of leadership, particularly in the field of nursing. 33 The discussed models of combining clinical and research activities in various health fields were collaboration, partnership, and integration. [34][35][36][37] However, the process of routinisation of RCTs in clinical practice has not been discussed as a holistic process and as a separate model, including in the field of wound management.…”
Section: Introductionmentioning
confidence: 99%